Montessori Education at a Distance, Part 1: A Survey of Montessori Educators’ Response to a Global Pandemic - Murray, Angela K.; Brown, Katie; Barton, Patricia (Journal of Montessori Research, 2021)
The transition to distance learning in the spring of 2020 caused by COVID-19 was particularly challenging for Montessori educators and students because key elements of the Method were not directly transferable to this new and hastily designed format. Hands-on learning with Montessori materials and learning in a community, as well as careful teacher observation, could not be easily replicated when children were learning from home. To understand how educators applied Montessori principles to serve children and families in these highly unusual circumstances, we surveyed Early Childhood and Elementary Montessori teachers about how they translated core elements of Montessori education to a distance-learning environment. The overall results suggest that Montessori distance-learning arrangements balanced live videoconference experiences for children with offline hands-on activities, while also relying on parents’ and caregivers’ involvement. Teachers reported that they largely designed learning experiences themselves, without significant support or guidance from school leaders. Still, teachers reported that they were able to uphold Montessori principles to only a moderate degree under the circumstances. While teachers understandably hunger for support, professional connections, and a return to the classroom experiences that drew them to the field of Montessori education, this study highlights factors that may affect the transition back to school for teachers, parents and caregivers, and students when face-to-face instruction resumes for all children.